'Big D' and 'little d': two types of twenty-first century development?. Issue 11 (2nd November 2019) - Lewis, David
Abstract: Confusion between the idea of development as purposeful intervention and development as outcome has been addressed by efforts to distinguish 'intentional' from 'immanent' development, and the distinction between 'big D' development as Western post- World War Two modernisation in the Global South, and 'little d' as the creation of winners and losers within unfolding capitalist change. As a heuristic device this distinction has been put to a variety of uses within development studies, but it has rarely been subjected to further scrutiny. This paper asks (1) whether the distinction remains coherent or risks being stretched too far, and (2) whether it remains relevant within the changing landscape of twenty-first century development. It first traces the historical evolution of the distinction, and then presents an exploratory case study of Bangladesh's garment sector in order to analyse the relationship between the two kinds of development empirically, identifying a number of contradictions and ambiguities. It finds that while the 'D/d' distinction remains useful at a general level, further conceptualisation is now needed, and its relevance may fade as the significance of Western aid declines.